Survei Implementasi Pembelajaran Pendidikan Jasmani Berdasarkan Kurikulum 2013 Di SMP Se Kecamatan Kertosono - Purnomo Adi Pratama; Budiman Agung Pratama; Setyo Harmono; Septyaning Lusianti (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2020)
Education is a mandatory requirement that must be possessed by every human being, until whenever education is needed by every individual human to fulfill the needs and perfect themselves as people who are knowledgeable, moral, and useful in a national development. This type of research uses quantitative descriptive research. Ali Maksum (2012: 68) descriptive research is research that is conducted to describe the real occurrence of circumstances. the results of the study obtained the implementation of the 2013 curriculum in physical education in the Junior High School in the Kertosono Subdistrict. the